2009
DOI: 10.1194/jlr.r800038-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid cytochrome P450 epoxygenase pathway

Abstract: Cytochrome P450 (CYP) epoxygenases convert arachidonic acid to four epoxyeicosatrienoic acid (EET) regioisomers, 5,6-, 8,9-, 11,12-, and 14,15-EET, that function as autacrine and paracrine mediators. EETs produce vascular relaxation by activating smooth muscle large-conductance Ca 21 -activated K 1 channels (BK Ca ). In addition, they have anti-inflammatory effects on blood vessels and in the kidney, promote angiogenesis, and protect ischemic myocardium and brain. CYP epoxygenases also convert eicosapentaenoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
313
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(320 citation statements)
references
References 51 publications
4
313
0
3
Order By: Relevance
“…Increasing the desaturation of C18 fatty acids seemed to greatly facilitate their epoxidation (Table 1). We have confirmed this result by incubating [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linoleic and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linolenic acids in the presence of cumene hydroperoxide and PXG4. Epoxidation occurred readily, i.e.…”
Section: Pxg4 Is a Regioselective Peroxygenasesupporting
confidence: 64%
See 1 more Smart Citation
“…Increasing the desaturation of C18 fatty acids seemed to greatly facilitate their epoxidation (Table 1). We have confirmed this result by incubating [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linoleic and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linolenic acids in the presence of cumene hydroperoxide and PXG4. Epoxidation occurred readily, i.e.…”
Section: Pxg4 Is a Regioselective Peroxygenasesupporting
confidence: 64%
“…The biosynthesis of these metabolites involves various cytochrome P450 isoforms that oxidize unsaturated fatty acids into a multitude of bioactive epoxygenated fatty acid (EFA) regioisomers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpolarizing effect that results due to the activation of BK Ca channels will lead to relaxation of the smooth muscle in the vasculature, causing hyperpolarization of the vascular smooth muscle and consequently vasorelaxation. Therefore, EETs are recognized to act as ‘endothelium‐derived hyperpolarizing factor’ (EDHF) in several components of the vasculature such as the renal and coronary blood vessels, resulting in reduction of the blood pressure 1, 2. Several effects of EET have been shown to occur due to its binding to a membrane receptor which leads to the activation of ion channels and signalling transduction pathways 2.…”
Section: Introductionmentioning
confidence: 99%
“…Several effects of EET have been shown to occur due to its binding to a membrane receptor which leads to the activation of ion channels and signalling transduction pathways 2. It is also reported that cells can take up EETs and integrate them into phospholipids, binding to cytosolic proteins and nuclear receptors 1. It is possible that they contribute to the pathogenesis of several disorders 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation